MyoD-induced reprogramming of human fibroblasts and urinary stem cells in vitro: protocols and their applications - Rossi, Rachele; Torelli, Silvia; Ala, Pierpaolo; Weston, William; Morgan, Jennifer; Malhotra, Jyoti; Muntoni, Francesco (Frontiers in Physiology, 2023)
The conversion of fibroblasts into myogenic cells is a powerful tool to both develop and test therapeutic strategies and to perform in-depth investigations of neuromuscular disorders, avoiding the need for muscle biopsies. We developed an easy, reproducible, and high-efficiency lentivirus-mediated transdifferentiation protocol, that can be used to convert healthy donor fibroblasts and a promising new cellular model, urinary stem cells (USCs), into myoblasts, that can be further differentiated into multinucleated myotubes in vitro. Transcriptome and proteome profiling of specific muscle markers (desmin, myosin, dystrophin) was performed to characterize both the myoblasts and myotubes derived from each cell type and to test the transdifferentiation-inducing capacity of MYOD1 in fibroblasts and USCs. Specifically, the Duchenne muscular dystrophy (DMD) transcripts and proteins, including both the full-length Dp427 and the short Dp71 isoform, were evaluated. The protocol was firstly developed in healthy donor fibroblasts and USCs and then used to convert DMD patients’ fibroblasts, with the aim of testing the efficacy of an antisense drug in vitro. Technical issues, limitations, and problems are explained and discussed. We demonstrate that MyoD-induced-fibroblasts and USCs are a useful in vitro model of myogenic cells to investigate possible therapies for neuromuscular diseases.